Enzymatic polymerization designed alpha-1, 3 glucan particle morphology as reinforcing fillers of dipped and casted rubber films. (1st September 2021) - Adibi, Azin; Kim, James; Mok, Jorge; Lenges, Christian; Simon, Leonardo; Mekonnen, Tizazu H.
Abstract: In this work, enzymatic polymerization derived microcrystalline glucan (MCG) polysaccharides fillers were employed as novel sustainable fillers of natural rubber (NR) films. MCG has a designed platelet morphology, with high crystallinity and colloidal stability in aqueous media and rubber lattices. NR films composed of 0–10 phr MCG were then fabricated using dipping and casting processes. The incorporation of MCG in the NR led to a remarkable enhancement in the tear strength, tensile properties, toughness, and an increase in water vapor permeability but a decrease in ethanol permeation. This behavior is appealing in gloves, where high sweat permeation from hands to the environment and limited to no solvent penetration from the environment to the skin is desired. The study indicated that the enzymatically polymerized MCG are effective reinforcing fillers for NR latex and potentially other elastomers offering the potential for appealing physical property improvements. Highlights: Designed polysaccharide particles via enzymatic polymerization Sustainable, highly crystalline, low density and aqueous colloidal polysaccharide Casted and dipped natural rubber film composites Effect of particle morphology on vapor permeation through rubber films